The filmmaker's apprentice and other stories - Schlesinger, Kira (Department of English Language and Literature, 2014)
"The Filmmaker's Apprentice and Other Stories" is a novella and six short stories set in a contemporary South Africa more complicated than ever, where people are constantly moving, young people are trying to forge identities and an older generation struggles to adapt to a radically altered reality. Characters struggle to relate meaningfully across socioeconomic, gender, national and racial divisions, bumping up against their own prejudices and perceptions in a way that makes it difficult to really see each other.